Simultaneous ATCs determination using pareto based evolutionary programming technique / M. Murtadha Othman ...[et al.] - Othman, M. Murtadha; Musirin, Ismail; Ilias, Sarizan; Mohamed, Azah; Hussain, Aini (UiTM Press, 2008)
This paper presents a new approach to determine simultaneous available transfer capability (ATC) for two transfer cases. Simultaneous determination of power transfer for two or more transfer cases involved intricate ATC calculations that yield to a lengthy computational time. Therefore, the Pareto based evolutionary programming (EP) is used to overcome the intricacy in calculating the optimum value of ATC with a fast computational time. The multi-objective function for the Pareto based EP technique is the ATC for two transfer cases and power flow limitation is considered as the fitness function of EP. The effectiveness of Pareto based EP technique in determining the ATCs are validated based on a case study of IEEE 24 bus system. The ATC is determined for the transfer cases from selling areas 1 and 2 to a buying area 3 and also from selling areas 1 and 3 to a buying area 2.